Pengembangan Mading Digital dan Literasi Digital Berbasis Wordpress di SMA N 1 2X11 Enam Lingkung - Dina Fitria Handayani; Ayu Atikah; Ivoni Amelia; Mutiara Mutiara; Ledya Guska Dewi; Sawalichia Kusuma Ningrum; Wendrizal Wendrizal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
the development of technology requires the world of education to face the optimal use of digital media. This article is quoted to describe the process of making and utilizing WordPress -based digital bulletin board in SMAN 1 2 × 11 six environment as a medium of expression, information, and memorization of digital literacy of students. The method of implementing activities includes training in the use of WordPress, the formation of an editorial team, technical assistance in making digital bulletin board, content of content publications. The results show that students are able to create a wordpress account, choose the appropriate theme, lock the content of the article, and distribute digital bulletin links online. In addition, this activity increases the ability of student digital literacy and encourages collaboration between students in managing school information. Digital Mading is proven to be an innovative and effective learning medium in fostering the 21st century skills. This article is expected to be a reference for other educators in integrating digital technology in school literacy activities.